DEA Sebagai Metode Alternatif Untuk Menilai Produktivitas Lembaga Pembiayaan Mikro - R. Nugroho Purwantoro (Jurnal Manajemen dan Usahawan Indonesia, 2020)
The objective of this paper is to introducing alternative method for evaluating performance of Indonesia microfinance institution with Data Envelopment Analysis (DEA).